Nano LiFePO4 in reduced graphene oxide framework for efficient high-rate lithium storage - Mun, Junyoung; Ha, Hyung-Wook; Choi, Wonchang (ELSEVIER SCIENCE BV, 2014)
In this paper, we report a simple sol-gel method for the synthesis of a composite containing reduced graphene oxide (R-GO) embedded within nano LiFePO4 particles for a lithium-ion battery cathode. This composite has an effective electron pathway and a highly meso-porous structure as compared to conventional LiFePO4. Highly conductive R-GO, together with the meso-porosity results in a material that has good electronic conductivity and high electrolyte permeability. Electrodes fabricated from the composite exhibited excellent performance when evaluated as lithium-ion battery cathodes, including compared to pristine LiFePO4. The electrode of the R-GO composite exhibits excellent rate capabilities of 125 mAh g(-1) at 10 C, whereas pristine LiFePO4 could deliver only 81.5 mAh g(-1) at the same condition. It also achieves an improved cyclability with capacity retention ratios of 92.48% after 200 cycles at 10 C, as well. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: COMPOSITE CATHODE MATERIAL; ION BATTERIES; ELECTROCHEMICAL CHARACTERIZATION; SECONDARY BATTERIES; HIGH-POWER; PERFORMANCE; ROUTE; NANOCOMPOSITE; SPECTROSCOPY; REDUCTION